A Reappraisal of the Necessity of a Ventriculoperitoneal Shunt After Decompressive Craniectomy in Traumatic Brain Injury - Seunghan Yu; Hyuk Jin Choi; Jung Hwan Lee; Mahnjeong Ha; Byung Chul Kim (Journal of Trauma and Injury)
Purpose Cranioplasty itself is believed to have therapeutic effects on hydrocephalus. The goal of this study was to evaluate the hypothesis that not every patient with hydrocephalus after decompressive craniectomy needs cerebrospinal fluid diversion, and that cranioplasty should be performed before considering cerebrospinal fluid diversion. Methods Data were collected from 67 individual traumatic brain injury patients who underwent cranioplasty between January 1, 2019 and December 31, 2019. Patients’ clinical and radiographic progression was reviewed retrospectively based on their medical records. Results Twenty-two of the 67 patients (32.8%) had ventriculomegaly on computed tomography scans before cranioplasty. Furthermore, 38 patients showed progressive ventriculomegaly after cranioplasty. Of these 38 patients, only six (15.7%) showed worsening neurologic symptoms, which were improved by the tap test; these patients eventually underwent ventriculoperitoneal shunt placement. Conclusions Cerebrospinal fluid diversion is not always required for radiologically diagnosed ventriculomegaly in traumatic brain injury patients after decompressive craniectomy. A careful clinical and neurologic evaluation should be conducted before placing a shunt.